PENGARUH PENDIDIKAN AKHLAK DALAM KELUARGA TERHADAP KEPRIBADIAN REMAJA AWAL (USIA 12-15 TAHUN) - Nurwidia, Ita; Anwar, Saeful (THORIQOTUNA: Jurnal Pendidikan Islam, 2020)
This study aims to determine the effect of moral education in the family on the personality of early adolescents (aged 12-15 years). The method used in this research is descriptive method through a quantitative approach, namely research that seeks to reveal the current state / condition by considering past conditions through processing the numbers obtained from the study. The population in this study were 135 people and the sample was 34 people. Based on the results of data processing that the effect of moral education in the family on the personality of early adolescents (aged 12-15 years) based on the rs price, the value of 0.64 on the Guilford scale is obtained in the interval 0.61 - 0.80 with high classification. Then the hypothesis testing of the effect of moral education in the family affects the personality of early adolescents (aged 12-15 years), it can be explained that the tcount value is greater than t table (tcount = 4.672> ttable = 1.69389, so that Ha is accepted and Ho is rejected), thus It can be explained that the more moral education in the family, the better the personality of early adolescents (ages 12-15 years).